Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element using the same
Through a specific liquid crystal alignment agent formulation, combined with the polymerization reaction of diamine and tetracarboxylic acid, the existing liquid crystal alignment film takes into account the DC brightness and speed and transmittance, and achieves efficient display performance of liquid crystal display components.
Patent Information
- Application Number
- CN202080011835.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-29
- Filing Date
- 2020-01-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-01-29
AI Technical Summary
When the existing liquid crystal alignment films take into account the rapid DC brightness and suppress the flicker change, they usually cannot maintain the high transmittance of the substrate at the same time, and when using low-resistance materials, charge accumulation is easily caused, affecting the display quality.
A specific liquid crystal alignment agent is used, including polyamic acid, polyamic acid ester or polyimide obtained by polymerization of diamine and tetracarboxylic acid, and a polymer formed by combining specific diamine and tetracarboxylic acid derivatives. , to ensure that the liquid crystal alignment film can maintain high transmittance and fast DC brightness relieving speed when using low resistance materials.
The high transmittance and rapid DC brightness ease of the liquid crystal orientation film under low resistance material conditions are achieved, which reduces charge accumulation and improves the display quality of the liquid crystal display element.
Smart Images

Figure FDA0004929650610000011 
Figure FDA0004929650610000021 
Figure FDA0004929650610000022
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal alignment agent, a liquid crystal alignment film, and a liquid crystal display element using the liquid crystal alignment film. Background Art
[0002] As a liquid crystal alignment film for liquid crystal display elements, a polyimide resin film is widely used. The polyimide liquid crystal alignment film is prepared by applying a liquid crystal alignment agent having a polymer such as polyamide acid (also called polyamic acid), polyamic acid ester, polyimide, and a solvent as a main component to a substrate.
[0003] In recent years, the high performance and large area of liquid crystal display elements, the power saving of display devices, etc. have been promoted. In addition, liquid crystal display elements have gradually been used in various environments, and various problems have become prominent. For example, static electricity is easy to accumulate in the liquid crystal box, and the charge accumulated in the liquid crystal alignment film will affect the display in the form of disordered liquid crystal orientation and residual image, significantly reducing the display quality level of the liquid crystal display element. In addition, when the liquid crystal panel is driven for a long time, due to the accumulation of charge generated by the drive, the size of the flicker (flicker) changes by applying positive and negative asymmetric voltages.
[0004] Patent Documents 1 to 4 describe a liquid crystal aligning agent containing a polyamic acid obtained from a low-resistance material such as 4,4′-diaminodiphenylamine (DADPA).
[0005] However, if a low-resistance material is used when manufacturing polyamic acid, the DC brightness relaxation speed becomes faster, but sometimes the flicker change becomes larger. On the contrary, if a material that suppresses the flicker change is used when manufacturing polyamic acid, the DC brightness relaxation speed sometimes becomes slower. That is, in the previous liquid crystal alignment film, the fast DC brightness relaxation speed and the suppression of flicker change are in a trade-off relationship, and sometimes it is impossible to have both, which becomes a problem.
[0006] In addition, when a low-resistance material is used, the transmittance of the substrate may be reduced due to coloring, which may be a problem.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 5900328
[0010] Patent Document 2: International Publication No. 2018 / 062440
[0011] Patent Document 3: Japanese Patent No. 6280701
[0012] Patent Document 4: Japanese Patent No. 6314488 Summary of the invention
[0013] Problems to be solved by the invention
[0014] The present invention is completed in view of the above situation, and its purpose is to provide a liquid crystal alignment agent that can obtain a liquid crystal alignment film that has both fast DC brightness relaxation speed and suppressed flicker changes. In addition, the purpose of the present invention is to provide a liquid crystal alignment agent that can obtain a liquid crystal alignment film with high transmittance of a substrate even when a low-resistance material is used.
[0015] Solutions for solving problems
[0016] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above-mentioned problems. As a result, the inventors have found that the above-mentioned problems can be satisfied by a specific liquid crystal aligning agent.
[0017] A liquid crystal aligning agent, characterized by containing: the following polymer (A), polymer (B) and polymer (C).
[0018] Polymer (A): at least one polymer selected from the group consisting of the following (i) to (iii).
[0019] (i) A polyamic acid obtained by polymerizing a diamine component containing at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the following formula [2], wherein the tetracarboxylic acid component consists of an aromatic tetracarboxylic dianhydride.
[0020] (ii) Polyamic acid ester obtained by polymerizing a diamine component and a tetracarboxylic acid component containing at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the following formula [2].
[0021] (iii) A polyimide obtained by imidating a polyimide precursor obtained by polymerizing a diamine component and a tetracarboxylic acid component, wherein the diamine component contains at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the following formula [2].
[0022]
[0023] (In formulas [1] and [2], A1 is a single bond, an ether bond, an ester bond, -C=C-, -C≡C-, an alkylene group having 2 to 20 carbon atoms, or a group in which a part or all of -CH2- in the alkylene group is substituted by at least one group selected from the group consisting of an ether bond, an ester bond, -C=C-, -C≡C-, a cyclohexylene group, and a phenylene group, a cyclohexylene group, or a phenylene group. A2 is a fluorine atom or an alkyl or alkoxy group having 1 to 5 carbon atoms (wherein any hydrogen atom of the alkyl or alkoxy group is optionally substituted by a fluorine atom). a is an integer from 0 to 4. When a is an integer greater than 2, A2 may be the same or different. b and c are each independently an integer from 1 to 2.)
[0024] Polymer (B): at least one polymer selected from the group consisting of a polyimide precursor obtained by polymerization reaction of a diamine component and a tetracarboxylic acid component, and a polyimide obtained from the polyimide precursor, wherein the diamine component contains a diamine represented by the following formula [3].
[0025] H2N-X-NH2 [3]
[0026] (wherein, X has a structure in which an aromatic hydrocarbon ring is bonded to a carbon atom constituting a five-membered or six-membered nitrogen-containing aromatic heterocyclic ring, or has a structure represented by the following formula,
[0027]
[0028] * Bonded to a structure other than a carbonyl group, and at least one bonded to an aromatic ring group.)
[0029] Polymer (C): A polyamic acid obtained by polymerizing a diamine component (wherein the diamine component does not contain the diamine represented by the formula [3]) and a tetracarboxylic acid component composed of an alicyclic tetracarboxylic dianhydride and / or an aliphatic tetracarboxylic dianhydride.
[0030] Effects of the Invention
[0031] According to the liquid crystal alignment agent of the present invention, a liquid crystal alignment film having both a fast DC brightness relaxation speed and suppressed flicker change can be obtained. In addition, according to the liquid crystal alignment agent of the present invention, a liquid crystal alignment film having a high transmittance of the substrate can be obtained even when a low resistance material is used. DETAILED DESCRIPTION
[0032] <Polymer (A)>
[0033] The polymer (A) contained in the liquid crystal aligning agent of this invention is the following polymer.
[0034] Polymer (A): at least one polymer selected from the group consisting of the following (i) to (iii).
[0035] (i) A polyamic acid obtained by polymerizing a diamine component containing at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the following formula [2], wherein the tetracarboxylic acid component consists of an aromatic tetracarboxylic dianhydride.
[0036] (ii) Polyamic acid ester obtained by polymerizing a diamine component and a tetracarboxylic acid component containing at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the formula [2].
[0037] (iii) A polyimide obtained by imidating a polyimide precursor obtained by polymerizing a diamine component and a tetracarboxylic acid component, wherein the diamine component contains at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the following formula [2].
[0038]
[0039] (In formulas [1] and [2], A1 is a single bond, an ether bond, an ester bond, -C=C-, -C≡C-, an alkylene group having 2 to 20 carbon atoms, or a group in which a part or all of -CH2- in the alkylene group is substituted by at least one group selected from the group consisting of an ether bond, an ester bond, -C=C-, -C≡C-, a cyclohexylene group, and a phenylene group, a cyclohexylene group, or a phenylene group. A2 is a fluorine atom or an alkyl or alkoxy group having 1 to 5 carbon atoms (wherein any hydrogen atom of the alkyl or alkoxy group is optionally substituted by a fluorine atom). a is an integer from 0 to 4. When a is an integer greater than 2, A2 may be the same or different. b and c are each independently an integer from 1 to 2.)
[0040] (Diamine component for producing polymer (A))
[0041] The diamine component used for producing the polymer (A) contains at least one diamine selected from the group consisting of the diamine represented by the above formula [1] and the diamine represented by the formula [2].
[0042] In the above formulas [1] to [2], it is preferred that A1 is a single bond, -C=C-, -C≡C-, an alkylene group having 2 to 10 carbon atoms, or a group in which a part or all of the -CH2- in the alkylene group is substituted by at least one group selected from the group consisting of an ether bond, an ester bond, -C=C-, -C≡C-, a cyclohexylene group and a phenylene group, a cyclohexylene group or a phenylene group, A2 is CH3, a is an integer from 0 to 1, b is 1, and c is an integer from 1 to 2.
[0043] Examples of the diamines represented by formula [1] and formula [2] include the following diamines.
[0044]
[0045]
[0046] The amount of the diamine represented by formula [1] and [2] used is 30 to 100 mol %, more preferably 40 to 100 mol %, and even more preferably 50 to 100 mol % based on the total amount of the diamine component used to produce the polymer (A).
[0047] In addition, as the diamine component for producing the polymer (A) contained in the liquid crystal aligning agent of the present invention, any diamine other than the diamine represented by formula [1] and [2] (hereinafter also referred to as "other diamine") can be used. Specific examples of other diamines include: 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4-(2-(methylamino)ethyl)aniline, 4-(2-aminoethyl)aniline, 4,4'-diaminobenzophenone, 4,4'-diaminoazobenzene, 1-(4-aminophenyl)-1,3,3-trimethyl-1H-indane-5-amine, 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-indane-6-amine, 1 diamines having a photopolymerizable group at the end, such as 4-diaminonaphthalene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,7-diaminonaphthalene, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(4-aminophenyl)propane, 2-(2,4-diaminophenoxy)ethyl methacrylate, and 2,4-diamino-N,N-diallylaniline; cholesteryl (cholest diamines having a steroid skeleton such as 3,5-diaminobenzene, 3,5-diaminobenzoic acid cholesteryl ester, 3,5-diaminobenzoic acid cholesteryl ester, 3,5-diaminobenzoic acid lanosterol ester, 3,6-bis(4-aminobenzoyloxy)cholestane; diamines represented by the following formulas (V-1) to (V-6); Diamines having a siloxane bond such as 1,3-bis(3-aminopropyl)-tetramethyldisiloxane; aromatic diamines such as diamines having a group "-N(D)-" (D represents a protective group which is detached by heating and replaced by a hydrogen atom, preferably a tert-butoxycarbonyl group) such as the following formulas (5-1) to (5-11); aliphatic diamines such as m-xylylenediamine, ethylenediamine, 1,3-propylenediamine, tetramethylenediamine, and hexamethylenediamine; alicyclic diamines such as p-cyclohexanediamine and 4,4'-methylenebis(cyclohexylamine).
[0048]
[0049] (In the above formulas (V-1) to (V-6), X v1 ~X v4 , X p1 ~X p8 Each independently represents -(CH2) a -(a is an integer of 1 to 15), -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -CH2O-, -CH2OCO-, -COO- or -OCO-, X v5 represents -O-, -CH2O-, -CH2OCO-, -COO- or -OCO-. Xa represents a single bond, -O-, -NH- or -O-(CH2) m -O- (m represents an integer from 1 to 6), R v1 ~R v4 , R 1a ~R 1b each independently represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms)
[0050]
[0051] (Boc represents tert-butoxycarbonyl.)
[0052] The diamine component used to produce the polymer (A) of the present invention can be used alone or in combination of two or more, depending on the solubility of the polymer (A) in a solvent, the coating properties of a liquid crystal aligning agent, the liquid crystal orientation when formed into a liquid crystal aligning film, the voltage holding ratio, the stored charge and other properties.
[0053] (Tetracarboxylic acid component for producing polymer (A))
[0054] The tetracarboxylic acid component of the (i) polyamic acid used for producing the polymer (A) consists of aromatic tetracarboxylic dianhydride.
[0055] Here, the aromatic tetracarboxylic dianhydride refers to an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups bonded to the same or different aromatic rings. In this case, if there is one aromatic ring, it is preferably an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups bonded to the aromatic ring. In addition, if there are two or more aromatic rings, it is preferably the following acid dianhydride: an acid dianhydride obtained by intramolecular dehydration of two carboxyl groups bonded to one aromatic ring and intramolecular dehydration of two carboxyl groups bonded to other aromatic rings; or an acid dianhydride obtained by intramolecular dehydration of a carboxyl group bonded to one of two adjacent aromatic rings and a carboxyl group bonded to another, and intramolecular dehydration of a carboxyl group bonded to one of two adjacent aromatic rings and a carboxyl group bonded to another.
[0056] As an aromatic tetracarboxylic dianhydride, the compound represented by following formula (3a-1) is mentioned, for example.
[0057]
[0058] In the above formula, X1 is any of the following formulae (A-1) to (A-28). * represents a bonding bond.
[0059]
[0060]
[0061] As the tetracarboxylic acid component for producing (ii) polyamic acid ester or (iii) polyimide of the polymer (A), any tetracarboxylic dianhydride or a derivative thereof (tetracarboxylic acid, tetracarboxylic acid dihalide, tetracarboxylic acid dialkyl ester, or tetracarboxylic acid dialkyl ester dihalide) can be used.
[0062] The tetracarboxylic acid component used to produce (ii) polyamic acid ester or (iii) polyimide of polymer (A) is preferably composed of aromatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride or their derivatives. Aromatic tetracarboxylic dianhydride can include the above-mentioned aromatic tetracarboxylic dianhydride, and alicyclic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride can include alicyclic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride in polymer (C). Preferred specific examples of aromatic tetracarboxylic dianhydride used to produce (ii) polyamic acid ester or (iii) polyimide of polymer (A) include compounds represented by formula (3a-1), and preferred specific examples of alicyclic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride can include compounds represented by formula (3c-1) described below.
[0063] The tetracarboxylic acid component for producing the polymer (A) of the present invention can be used alone or in combination of two or more thereof, depending on the solubility of the polymer (A) in a solvent, the coating properties of a liquid crystal aligning agent, the liquid crystal alignment properties when formed into a liquid crystal aligning film, the voltage holding ratio, the stored charge and the like.
[0064] <Polymer (B)>
[0065] The polymer (B) contained in the liquid crystal aligning agent of this invention is the following polymer.
[0066] Polymer (B): at least one polymer selected from the group consisting of a polyimide precursor obtained by polymerization reaction of a diamine component and a tetracarboxylic acid component, and a polyimide obtained from the polyimide precursor, wherein the diamine component contains a diamine represented by the following formula [3].
[0067] H2N-X-NH2 [3]
[0068] (wherein, X has a structure in which an aromatic hydrocarbon ring is bonded to a carbon atom constituting a five-membered or six-membered nitrogen-containing aromatic heterocyclic ring, or has a structure represented by the following formula,
[0069]
[0070] * Bonded to a structure other than a carbonyl group, and at least one bonded to an aromatic ring group.)
[0071] It should be noted that "aromatic ring group" refers to an n-valent group formed by removing n hydrogen atoms from an aromatic ring, and specific examples of the aromatic ring include: benzene ring, naphthalene ring, anthracene ring, phenanthrene ring, pyrene ring, perylene ring and terylene ring. In addition, specific examples of the nitrogen-containing aromatic heterocyclic ring of the five-membered ring or six-membered ring include: pyrrole ring, pyridine ring, etc. Specific examples of aromatic hydrocarbon rings include: benzene ring, naphthalene ring, etc.
[0072] The diamine represented by the formula [3] preferably has structures represented by the following formulas [3-1] to [3-3].
[0073]
[0074] (In the formula, * represents a bond. In the formula [3-3], at least one of the bonds derived from the carbon atoms constituting the nitrogen-containing aromatic heterocyclic ring is bonded to the aromatic hydrocarbon ring.)
[0075] As examples of the diamine represented by formula [3], the following diamines can be mentioned.
[0076]
[0077] The amount of the diamine represented by formula [3] used is 30 to 100 mol %, more preferably 40 to 100 mol %, and even more preferably 50 to 100 mol % based on the total amount of the diamine component used in the polymer (B).
[0078] As the diamine component for producing the polymer (B) contained in the liquid crystal aligning agent of the present invention, any diamine other than the diamine represented by the formula [3], for example, the above-mentioned other diamine can be used.
[0079] The diamine component used to produce the polymer (B) of the present invention can be used alone or in combination of two or more, depending on the solubility of the polymer (B) in a solvent, the coating properties of a liquid crystal aligning agent, the liquid crystal orientation when formed into a liquid crystal aligning film, the voltage holding ratio, the stored charge and other properties.
[0080] As a tetracarboxylic acid component for producing the polymer (B) contained in the liquid crystal aligning agent of the present invention, any tetracarboxylic dianhydride or a derivative thereof can be used. As a more preferred specific example of the tetracarboxylic dianhydride for producing the polymer (B), there can be listed: aromatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride for producing the polymer (A). Preferred specific examples of aromatic tetracarboxylic dianhydride include compounds represented by the above formula (3a-1), and preferred specific examples of alicyclic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride include compounds represented by the following formula (3c-1) described later.
[0081] The tetracarboxylic acid component used for producing the polymer (B) of the present invention may be used alone or in combination of two or more thereof, depending on the solubility of the polymer (B) in a solvent, the coating properties of a liquid crystal aligning agent, the liquid crystal alignment properties when formed into a liquid crystal aligning film, the voltage holding ratio, the stored charge and other properties.
[0082] <Polymer (C)>
[0083] The polymer (C) contained in the liquid crystal aligning agent of this invention is the following polymer.
[0084] Polymer (C): A polyamic acid obtained by polymerizing a diamine component (wherein the diamine component does not contain the diamine represented by the formula [3]) and a tetracarboxylic acid component composed of an alicyclic tetracarboxylic dianhydride and / or an aliphatic tetracarboxylic dianhydride.
[0085] The diamine component used for producing the polymer (C) does not contain the diamine represented by the formula [3].
[0086] As a diamine component for producing a polymer (C), a diamine represented by the following formula [4] is mentioned, for example.
[0087] H2N-Y-NH2 [4]
[0088] (wherein, Y has any one or more of the structures shown in the following formulae,
[0089]
[0090] * is a bonding key. )
[0091] As a more preferred specific example of Y, a divalent organic group having at least one of the partial structures shown above and at least one benzene ring is preferred. If more preferred specific examples of the diamine represented by the formula [4] are listed, the diamines of the following formulas (4-1) to (4-2) are listed.
[0092]
[0093] (In the formula, A1 is a hydroxyl group, a carboxyl group, a fluorine atom, or an alkyl group or alkoxy group having 1 to 5 carbon atoms (wherein any hydrogen atom of the alkyl group or alkoxy group is optionally substituted by a fluorine atom), and at least one of A1 represents a hydroxyl group or a carboxyl group. A2 is a single bond, an ether bond, an ester bond, an alkylene group having 1 to 20 carbon atoms, a divalent organic group in which a part of the alkylene group having 1 to 20 carbon atoms is substituted by a urea bond or an amide bond, or a group in which a part or all of -CH2- in the divalent organic group is substituted by at least one group selected from the group consisting of an ether bond, an ester bond, a cyclohexylene group, and a phenylene group. a1 is an integer of 1 to 4. a21 and a22 are integers of 0 to 4. When a1, a21, or a22 is an integer greater than 2, A1 may be the same or different. When A2 represents a single bond or an alkylene group having 1 to 20 carbon atoms, either a21 or a22 is an integer other than 0. b and c are each independently an integer of 1 to 2.)
[0094] The diamine represented by the formula [4] is preferably the following diamine, and particularly preferably 1,3-bis(4-aminophenethyl)urea represented by the following formula.
[0095]
[0096] The diamine component used to produce the polymer (C) of the present invention can be used alone or in combination of two or more, depending on the solubility of the polymer (C) in a solvent, the coating properties of a liquid crystal aligning agent, the liquid crystal orientation when a liquid crystal aligning film is formed, the voltage holding ratio, the accumulated charge, and other properties. As the diamine component used to produce the polymer (C), any diamine other than the diamine represented by the formula [3] or the diamine represented by the formula [4] can be used, such as the other diamines.
[0097] The tetracarboxylic acid component for producing the polymer (C) is composed of alicyclic tetracarboxylic dianhydride and / or aliphatic tetracarboxylic dianhydride.
[0098] Here, aliphatic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups bonded to a chain hydrocarbon structure. However, it is not necessary to be composed of only a chain hydrocarbon structure, and a part thereof may have an alicyclic structure or an aromatic ring structure.
[0099] Alicyclic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups and at least one carboxyl group bonded to an alicyclic structure. Among them, none of these four carboxyl groups is bonded to an aromatic ring. In addition, it is not necessary to be composed only of an alicyclic structure, and a part of it may also have a chain hydrocarbon structure or an aromatic ring structure.
[0100] As aliphatic tetracarboxylic dianhydride or alicyclic tetracarboxylic dianhydride, the compound represented by following formula (3c-1) is mentioned, for example.
[0101]
[0102] In the above formula, X2 is any of the following formulae (B-1) to (B-18). * represents a bonding bond.
[0103]
[0104] The tetracarboxylic acid component used for producing the polymer (C) of the present invention may be used alone or in combination of two or more thereof, depending on the solubility of the polymer (C) in a solvent, the coating properties of a liquid crystal aligning agent, the liquid crystal orientation in the case of a liquid crystal aligning film, the voltage holding ratio, the stored charge and the like.
[0105] <Method for producing polymers (A) to (C)>
[0106] The polyimide precursor which can be contained in the liquid crystal aligning agent of this invention is a polyamic acid or a polyamic acid ester.
[0107] The reaction of the diamine component and the tetracarboxylic acid component is usually carried out in a solvent. The solvent used at this time is not particularly limited as long as it dissolves the generated polyimide precursor. Specific examples of the solvent used in the reaction are listed below, but are not limited to these examples.
[0108] For example, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropaneamide, 3-butoxy-N,N-dimethylpropaneamide, dimethyl sulfoxide, or 1,3-dimethyl-imidazolidinone can be mentioned. In addition, when the polyimide precursor has high solvent solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, etc. can be used.
[0109] These solvents can be used alone or in combination. Further, even if the solvent does not dissolve the polyimide precursor, it can be mixed with the solvent in the range where the generated polyimide precursor does not precipitate. In addition, the moisture in the solvent hinders the polymerization reaction, and then becomes the reason for hydrolyzing the generated polyimide precursor, so the solvent is preferably a dehydrated solvent.
[0110] When the diamine component and the tetracarboxylic acid component are reacted in a solvent, the following methods can be cited: a method of stirring a solution obtained by dispersing or dissolving the diamine component in a solvent and directly adding the tetracarboxylic acid component, or a method of dispersing or dissolving the tetracarboxylic acid component in a solvent and adding the diamine component; a method of adding the diamine component to a solution obtained by dispersing or dissolving the tetracarboxylic acid component in a solvent; a method of alternately adding the diamine component and the tetracarboxylic acid component to the reaction system, and any of these methods can be used. In addition, when a plurality of diamine components or tetracarboxylic acid components are used and reacted, they can be reacted in a premixed state, or they can be reacted separately in sequence, or low molecular weight substances reacted separately can be mixed and reacted to form a polymer.
[0111] The temperature for polycondensing the diamine component and the tetracarboxylic acid component can be selected from any temperature in the range of -20 to 150°C, preferably in the range of -5 to 100°C. The reaction can be carried out at any concentration, but if the concentration is too low, it becomes difficult to obtain a high molecular weight polymer, and if the concentration is too high, the viscosity of the reaction solution becomes too high and it is difficult to stir uniformly. Therefore, the concentration of the polymer is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. The reaction is carried out at a high concentration in the early stage, and a solvent can be added thereafter.
[0112] In the polymerization reaction to obtain the polyimide precursor, the total molar ratio of the tetracarboxylic acid component to the total molar ratio of the diamine component is preferably 0.8 to 1.2. As in a normal polycondensation reaction, the closer this molar ratio is to 1.0, the greater the molecular weight of the generated polyimide precursor.
[0113] The polyimide is obtained by ring-closing a polyimide precursor. In the polyimide, the ring-closing ratio (also referred to as the imidization ratio) of the amic acid group (amide acid group) does not necessarily need to be 100%, and can be arbitrarily adjusted according to the application and purpose.
[0114] As a method of imidating a polyimide precursor, thermal imidation which heats the solution of a polyimide precursor as it is, and catalyst imidation which adds a catalyst to the solution of a polyimide precursor are mentioned.
[0115] The temperature when the polyimide precursor is thermally imidized in a solution is preferably 100 to 400° C., more preferably 120 to 250° C., and a method in which the imidization reaction is carried out while removing water generated by the imidization reaction to the outside of the system is preferred. Catalytic imidization of the polyimide precursor can be carried out by adding a basic catalyst and an acid anhydride to a solution of the polyimide precursor and stirring at −20 to 250° C., preferably 0 to 180° C.
[0116] The amount of the basic catalyst is preferably 0.5 to 30 times, more preferably 2 to 20 times, the amount of the amic acid group. The amount of the acid anhydride is preferably 1 to 50 times, more preferably 3 to 30 times, the amount of the amic acid group.
[0117] Examples of the basic catalyst include pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. Among them, pyridine is preferred because it has a moderate basicity that allows the reaction to proceed.
[0118] Examples of acid anhydrides include acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. In particular, acetic anhydride is preferred because purification after the reaction is easy. The imidization rate obtained by catalytic imidization can be controlled by adjusting the amount of catalyst, reaction temperature, and reaction time.
[0119] When the polyimide precursor generated by the reaction solution or the polyimide obtained therefrom is recovered, the reaction solution is added to a solvent to precipitate it. As solvents for precipitation, methanol, ethanol, isopropanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, toluene, benzene, water, etc. are listed. After the polymer precipitated by the solvent is filtered and recovered, it can be dried at normal pressure or reduced pressure, at room temperature or by heating. In addition, if the operation of dissolving the precipitated polymer recovered in a solvent again and reprecipitating and recovering is repeated 2 to 10 times, the impurities in the polymer can be reduced. As solvents at this time, for example, alcohols, ketones, hydrocarbons, etc. are listed. If three or more solvents selected from them are used, the efficiency of purification is further increased, so it is preferred.
[0120] In the present invention, when the polyimide precursor is polyamic acid ester, examples of a specific method for producing the polyimide precursor include the method described in paragraphs
[0054] to
[0062] of International Publication No. WO2011-115077.
[0121] The polyimide precursor or the polyimide obtained therefrom may be terminal-modified by a terminal-modifying agent. By modifying the terminal, the effect of improving the adhesion between the sealant and the liquid crystal alignment film can be obtained.
[0122] Examples of the terminal modification agent include tert-butyloxycarbonylating agents, such as N-tert-butyloxycarbonylimidazole, tert-butylphenyl carbonate, tert-butyl carbazate, tert-butyl chloroformate, di-tert-butyl dicarbonate, etc. As the terminal modification agent, di-tert-butyl dicarbonate is preferred.
[0123] <Liquid crystal alignment agent>
[0124] An embodiment of the present invention is a liquid crystal aligning agent containing a polymer (A), a polymer (B), and a polymer (C).
[0125] From the viewpoint of the alignment regulating force of a liquid crystal, content of the polymer (A) in the liquid crystal aligning agent is preferably 10 to 50 mass %, more preferably 10 to 30 mass %, with respect to 100 mass % of the total amount of the polymers (A) to (C).
[0126] From the viewpoint of the relaxation property of the stored charge, content of the polymer (B) in the liquid crystal aligning agent is preferably 10 to 70 mass %, more preferably 40 to 60 mass %, with respect to 100 mass % of the total amount of the polymers (A) to (C).
[0127] From the viewpoint of the DC storage charge amount, content of the polymer (C) in the liquid crystal aligning agent is preferably 10 to 50 mass %, more preferably 10 to 30 mass %, with respect to 100 mass % of the total amount of the polymers (A) to (C).
[0128] The liquid crystal aligning agent of the present invention may also contain other polymers other than polymers (A) to (C). Other polymers include cellulose polymers, acrylic polymers, methacrylic polymers, polystyrene, polyamide, polysiloxane, etc. The content of other polymers is preferably 0.5 to 15 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total of polymers (A) to (C).
[0129] Moreover, a liquid crystal aligning agent usually contains an organic solvent, and content of the organic solvent is preferably 70-99.9 mass % with respect to the liquid crystal aligning agent. This content can be appropriately changed according to the coating method of the liquid crystal aligning agent and the film thickness of the target liquid crystal aligning film.
[0130] The organic solvent used in the liquid crystal alignment agent is preferably a solvent (also referred to as a good solvent) that dissolves the polymers (A) to (C). For example, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, 3-methoxy-N,N-dimethylpropaneamide, 3-butoxy-N,N-dimethylpropaneamide, etc. are listed. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropaneamide, 3-butoxy-N,N-dimethylpropaneamide or γ-butyrolactone is preferably used.
[0131] The good solvent in the liquid crystal aligning agent of the present invention is preferably 20 to 99% by mass of the whole solvent contained in the liquid crystal aligning agent, more preferably 20 to 90% by mass, particularly preferably 30 to 80% by mass.
[0132] The liquid crystal aligning agent of the present invention can use a solvent (also referred to as a poor solvent) that improves the coating properties and surface smoothness of the liquid crystal aligning film when the liquid crystal aligning agent is applied. Specific examples thereof are given below.
[0133] For example, diisopropyl ether, diisobutyl ether, diisobutyl carbinol (2,6-dimethyl-4-heptanol), ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, ethylene glycol monobutyl ether, ethylene glycol monoisopentyl ether, ethylene glycol monohexyl ether, propylene glycol monobutyl ether, 1-(2-butoxyethoxy)-2-propanol, 2 -(2-Butoxyethoxy)-1-propanol, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, propylene glycol diacetate, n-butyl acetate, propylene glycol monoethyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, propyl 3-methoxypropionate, butyl 3-methoxypropionate, n-butyl lactate, isopentyl lactate, diethylene glycol monoethyl ether, diisobutyl ketone (2,6-dimethyl-4-heptanone), etc.
[0134] Among them, preferred combinations of solvents include: N-methyl-2-pyrrolidone and ethylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone and ethylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone and propylene glycol monobutyl ether; N-ethyl-2-pyrrolidone and propylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone, 4-hydroxy-4-methyl-2-pentanone and diisopropyl ether. Ethylene glycol diethyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanone; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and diisopropyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanol; N-methyl-2-pyrrolidone, γ-butyrolactone and dipropylene glycol dimethyl ether; etc. These poor solvents are preferably 1 to 80% by mass of the total solvent contained in the liquid crystal alignment agent, more preferably 10 to 80% by mass, and particularly preferably 20 to 70% by mass. The type and content of such solvents can be appropriately selected according to the coating device, coating conditions, coating environment, etc. of the liquid crystal alignment agent.
[0135] The liquid crystal alignment agent of the present invention may also contain: a dielectric for the purpose of changing the electrical properties of the liquid crystal alignment film, such as the dielectric constant and conductivity; a silane coupling agent for the purpose of improving the adhesion between the liquid crystal alignment film and the substrate; a cross-linking compound for the purpose of improving the hardness and density of the film when the liquid crystal alignment film is made; and an imidization accelerator for the purpose of efficiently carrying out the imidization by heating the polyimide precursor when the coating film is fired.
[0136] Examples of compounds for improving the adhesion between the liquid crystal alignment film and the substrate include compounds containing functional silanes and compounds containing epoxy groups, for example, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-( 2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltriethoxysilane, N-triethoxysilylpropyltriethylenetriamine, N-trimethoxysilylpropyltriethylenetriamine, 10-trimethoxysilyl-1,4,7-triazadecane, 10-triethoxysilyl-1,4,7-triazadecane, 9-trimethoxymethyl Silyl-3,6-diazanonyl acetate, 9-triethoxysilyl-3,6-diazanonyl acetate, N-benzyl-3-aminopropyl trimethoxysilane, N-benzyl-3-aminopropyl triethoxysilane, N-phenyl-3-aminopropyl trimethoxysilane, N-phenyl-3-aminopropyl triethoxysilane, N-bis(oxyethylene)-3-aminopropyl trimethoxysilane, N-bis(oxyethylene)-3-aminopropyl triethoxysilane, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, diol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, 1,3,5,6-tetraglycidyl-2,4-hexanediol, N,N,N',N',-tetraglycidyl-m-xylene diamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, or N,N,N',N',-tetraglycidyl-4,4'-diaminodiphenylmethane, etc.
[0137] Moreover, in order to improve the mechanical strength of a liquid crystal aligning film, you may add the following additives (CL-1) - (CL-15) to the liquid crystal aligning agent of this invention.
[0138]
[0139]
[0140] It is preferable that it is 0.1-30 mass parts with respect to 100 mass parts of the polymer component which the liquid crystal aligning agent contains content of the said additive, and it is more preferable that it is 0.5-20 mass parts.
[0141] <Method for producing liquid crystal alignment film>
[0142] The liquid crystal alignment film is obtained by coating the above-mentioned liquid crystal alignment agent on a substrate to form a coating, preferably drying it, and then firing it. As a substrate, a substrate with high transparency is preferred, and as its material, ceramics such as glass and silicon nitride; plastics such as acrylic and polycarbonate, etc. can be used. As a substrate, from the perspective of simplifying the process, it is preferred to use a substrate formed with an ITO (Indium Tin Oxide: indium tin oxide) electrode for driving liquid crystal. In addition, in a reflective liquid crystal display element, an opaque substrate such as a silicon wafer can be used as a substrate on one side, and its electrode can also use a light-reflecting material such as aluminum.
[0143] Industrially, screen printing, offset printing, flexographic printing, inkjet printing, etc. can be used to form a coating on a substrate using a liquid crystal aligning agent. In addition, dipping, roll coating, slit coating, spin coating, spray coating, etc. can also be used depending on the purpose.
[0144] After a film of the liquid crystal alignment agent is formed on the substrate, the film is preferably dried by a heating unit such as a heating plate, a heat circulation oven, an IR (infrared) oven, etc., preferably at 30 to 120° C., more preferably at 50 to 120° C., for 1 minute to 10 minutes, more preferably 1 minute to 5 minutes, to evaporate the solvent.
[0145] When the imide precursor in the polymer is thermally imidized, the coating obtained from the liquid crystal aligning agent is then subjected to a calcination treatment by the same heating unit as the above-mentioned drying treatment, preferably at 120 to 250° C., more preferably at 150 to 230° C. The calcination treatment time varies depending on the calcination temperature, but is preferably 5 minutes to 1 hour, and more preferably 5 minutes to 40 minutes.
[0146] The thickness of the coating after the calcination treatment is not particularly limited. If it is too thin, the reliability of the liquid crystal display element may decrease, and if it is too thick, the resistance of the obtained liquid crystal alignment film may increase. Therefore, it is preferably 5 to 300 nm, and more preferably 10 to 200 nm.
[0147] After the calcination treatment, the obtained film is subjected to an orientation treatment. Examples of the orientation treatment method include a brushing treatment method and a photo-orientation treatment method.
[0148] As a specific example of photo-orientation treatment, radiation biased in a certain direction is irradiated to the surface of the coating. As radiation, ultraviolet rays or visible light with a wavelength of 100 to 800 nm can be used. Among them, ultraviolet rays with a wavelength of 100 to 400 nm are preferred, and ultraviolet rays with a wavelength of 200 to 400 nm are more preferred. In order to improve the orientation of the liquid crystal, the substrate coated with the liquid crystal orientation film can be heated at 50 to 250°C while irradiating it with ultraviolet rays. In addition, the irradiation amount of the radiation is preferably 1 to 10000 mJ / cm2. Among them, 100 to 5000 mJ / cm2 is preferred. The liquid crystal orientation film produced in this way can stably align the liquid crystal molecules in a certain direction.
[0149] The higher the extinction ratio of polarized ultraviolet light, the higher the anisotropy can be imparted, which is preferred. Specifically, the extinction ratio of linearly polarized ultraviolet light is preferably 10:1 or more, and more preferably 20:1 or more.
[0150] The coating film subjected to the alignment treatment may be further subjected to at least one treatment selected from the group consisting of a heat treatment and a contact treatment with a solvent.
[0151] The heat treatment after the alignment treatment can be performed by the same heating means as the drying treatment and the calcining treatment, preferably at 180 to 250° C., more preferably at 180 to 230° C. When the temperature of the heat treatment is within the above range, the contrast of the liquid crystal display element obtained by the obtained liquid crystal alignment film can be improved.
[0152] The time of the heat treatment varies depending on the heating temperature, but is preferably 5 minutes to 1 hour, more preferably 5 to 40 minutes.
[0153] The solvent used for the contact treatment with the solvent is not particularly limited as long as it is a solvent that dissolves impurities and the like adhering to the liquid crystal alignment film.
[0154] Specific examples include water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, cyclohexyl acetate, etc. Among them, water, 2-propanol, 1-methoxy-2-propanol or ethyl lactate are preferred from the perspective of versatility and safety of the solvent. Water, 1-methoxy-2-propanol or ethyl lactate is more preferred. These solvents may be one or more.
[0155] As the above-mentioned contact treatment, there can be cited: immersion treatment, spray treatment (also referred to as spray treatment). The treatment time in these treatments is preferably 10 seconds to 1 hour, and in particular, a scheme of immersion treatment for 1 to 30 minutes can be cited. In addition, the temperature during the contact treatment can be room temperature or heated, preferably 10 to 80°C, and 20 to 50°C can be cited. During the contact treatment, ultrasonic treatment or the like can also be performed as needed.
[0156] After the contact treatment, rinsing (also referred to as leaching) and drying using a low boiling point solvent such as water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, etc. may be performed. At this time, either leaching or drying may be performed, or both may be performed. The drying temperature is preferably 50 to 150° C., and 80 to 120° C. may be cited. In addition, the drying time is preferably 10 seconds to 30 minutes, and preferably 1 to 10 minutes.
[0157] After the contact treatment with the solvent, the heat treatment after the alignment treatment may be performed. By adopting such a configuration, a liquid crystal alignment film having excellent liquid crystal orientation can be obtained.
[0158] <Liquid crystal display device>
[0159] The liquid crystal alignment film of the present invention can be applied to various driving modes such as TN (Twisted Nematic) mode, STN (Super Twisted Nematic) mode, IPS (In-Plane Switching) mode, FFS (Fringe Field Switching) mode, VA (Vertical Alignment) mode, MVA (Multi-domain Vertical Alignment) mode, PSA (Polymer Sustained Alignment) mode, etc. It is preferably used as a liquid crystal alignment film for liquid crystal display elements of transverse electric field modes such as IPS mode and FFS mode, and is particularly useful as a liquid crystal display element of FFS mode. The liquid crystal display element of the present invention is an element made by preparing a liquid crystal box by a known method after obtaining a substrate with a liquid crystal alignment film from the above-mentioned liquid crystal alignment agent, and using the liquid crystal box.
[0160] As an example of a method for manufacturing a liquid crystal cell, a passive matrix liquid crystal display element is used as an example. It should be noted that an active matrix liquid crystal display element in which a conversion element such as a TFT (Thin Film Transistor) is provided in each pixel portion constituting an image display may also be used.
[0161] Specifically, a transparent glass substrate is prepared, a common electrode is provided on one substrate, and a segmented electrode is provided on the other substrate. These electrodes can be provided as ITO electrodes, for example, and patterned in a manner that enables the desired image display. Next, an insulating film is provided on each substrate in a manner that covers the common electrode and the segmented electrode. The insulating film can be provided as a film composed of SiO2-TiO2 formed by a sol-gel method, for example. Next, under the above conditions, a liquid crystal alignment film is formed on each substrate, and the substrate of one side is superimposed on the substrate of the other side in a manner that the liquid crystal alignment film faces face each other, and the periphery is bonded with a sealant. In order to control the gap between the substrates, it is usually preferred to mix spacers in the sealant. In addition, it is preferred to also scatter spacers for controlling the gap between the substrates in the in-plane portion where the sealant is not provided. In a portion of the sealant, an opening portion that can be filled with liquid crystal from the outside is pre-set.
[0162] Then, through the opening provided in the sealant, the liquid crystal material is injected into the space surrounded by the two substrates and the sealant. Then, the opening is sealed with an adhesive. As for injection, the following methods can be cited: vacuum injection method, method using capillary phenomenon in the atmosphere, and ODF (One Drop Fill: liquid crystal dripping) method can also be used. As the liquid crystal material, any one of positive and negative dielectric anisotropy can also be used. In the present invention, from the viewpoint of liquid crystal orientation, the liquid crystal with negative dielectric anisotropy is preferred, which can be used according to the purpose.
[0163] After the liquid crystal material is injected into the liquid crystal cell, the polarizing plate is placed. Specifically, it is preferable to bond a pair of polarizing plates to the surfaces of the two substrates on the opposite sides to the liquid crystal layer.
[0164] [Example]
[0165] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited thereto. The abbreviations of the following compounds and the methods for measuring the properties are as follows.
[0166] (Diamine)
[0167]
[0168] (Tetracarboxylic dianhydride)
[0169]
[0170] (Terminus Modifier)
[0171] Di-tert-butyl dicarbonate (Boc2O).
[0172] (additive)
[0173]
[0174] (s-1): 3-glycidoxypropyltriethoxysilane.
[0175] (Organic Solvent)
[0176] NMP: N-methyl-2-pyrrolidone.
[0177] GBL: gamma-butyrolactone.
[0178] BCS: Butyl Cellosolve.
[0179] <Measurement of Imidization Ratio>
[0180] Add 20 mg of polyimide powder to an NMR sample tube (NMR standard sampling tube, φ5 (manufactured by Kusano Scientific Co., Ltd.)), add deuterated dimethyl sulfoxide (DMSO-d6, 0.05% TMS (tetramethylsilane) mixture) (0.53 ml), and apply ultrasound to completely dissolve it. The solution was measured for 500 MHz proton NMR using an NMR measuring machine (JNW-ECA500) (manufactured by JEOL DATUM Co., Ltd.). The imidization rate was calculated as follows: a proton derived from a structure that does not change before and after imidization is determined as a reference proton, and the peak integral value of the proton and the proton peak integral value derived from the NH group of the amide acid appearing near 9.5 ppm to 10.0 ppm are used to calculate the rate using the following formula.
[0181] Imidization rate (%) = (1-α·x / y) × 100
[0182] In the above formula, x is the peak integral value of protons derived from NH groups of amic acid, y is the peak integral value of reference protons, and α is the ratio of the number of reference protons to protons of one NH group of amic acid in the case of polyamic acid (imidation ratio 0%).
[0183] [Synthesis of polymer]
[0184] <Synthesis example 1>
[0185] 10.3 g (42.5 mmol) of DA-1, 7.8 g (14.0 mmol) of DA-3, and 4.78 g (14.0 mmol) of DA-4 were weighed into a four-necked flask with a stirring device and a nitrogen inlet tube, and NMP was added in a manner that the solid content concentration became 15% by mass, and nitrogen was supplied while stirring to dissolve. While stirring the diamine solution, 10.2 g (45.5 mmol) of CA-1 was added, and NMP was further added in a manner that the solid content concentration became 18% by mass. After stirring at 40°C for 1 hour, 3.57 g (18.2 mmol) of CA-2 was added at room temperature, and NMP was further added in a manner that the solid content concentration became 18% by mass. The polymerization solution was stirred for 3 hours to obtain a polyamic acid solution (PA-I).
[0186] 100.0 g of the obtained polyamic acid solution (PA-I) was weighed into a 100 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, 4.06 g (18.6 mmol) of di-tert-butyl dicarbonate (Boc2O) as a terminal modification agent was added, and after stirring at 40°C for 15 hours, a terminal-modified polyamic acid solution (PAboc-I) was obtained.
[0187] 100.0 g of the terminal-modified polyamic acid solution (PAboc-I) obtained was weighed into a 100 mL four-necked flask with a stirring device and a nitrogen inlet tube, and NMP was added in a manner that the solid content concentration became 12% by mass, and stirred for 30 minutes. 10.54 g of acetic anhydride and 2.72 g of pyridine were added to the obtained polyamic acid solution, and after stirring at room temperature for 30 minutes, the mixture was heated and stirred at 55°C for 2 hours and 15 minutes to perform chemical imidization. The obtained reaction solution was added to 3.5 times the mass of the reaction solution in methanol while stirring, the precipitated precipitate was filtered, and then washed with methanol 3 times. The obtained resin powder was vacuum dried at 80°C for 12 hours to obtain a powder of polyimide (SPI1-1). The imidization rate of the polyimide resin powder was 75%. NMP was added to the obtained polyimide (SPI1-1) so as to have a solid content concentration of 15 mass %, and the mixture was stirred at 70° C. for 15 hours to obtain a solution of the polyimide (SPI1-1) having a solid content concentration of 15 mass %.
[0188] <Synthesis Examples 2 to 6>
[0189] The diamine and tetracarboxylic acid derivatives shown in Table 1 below were respectively implemented in the same order as in Synthesis Example 1, thereby obtaining solutions of polyimides (SPI1-1) to (SPI1-6) shown in Table 1 below. In Table 1, the numerical values indicated below the compound names indicate the mass (g) of the tetracarboxylic acid derivative used in the synthesis for the tetracarboxylic acid component and the mass (g) of the diamine used in the synthesis for the diamine acid component. For the terminal modification treatment, the case recorded as Boc2O was implemented in the same order as in Synthesis Example 1, and the case recorded as None was the case where the terminal modification treatment was not performed.
[0190] [Table 1]
[0191]
[0192] <Synthetic Examples 7 to 28>
[0193] Using the diamines and tetracarboxylic acid derivatives shown in Table 2 below, the same procedures as in Synthesis Example 1 were followed to obtain solutions of polyamic acids (PAA2-1 to PAA2-15, PAA3-1 to PAA3-7) shown in Table 1 below. In Table 2, the numerical values below the compound names indicate the mass (g) of the tetracarboxylic acid derivative used in the synthesis for the tetracarboxylic acid component and the mass (g) of the diamine used in the synthesis for the diamine acid component.
[0194] [Table 2]
[0195]
[0196] [Preparation of Liquid Crystal Alignment Agent]
[0197] <Example 1>
[0198] The solution of polyimide (SPI1-1) obtained in Synthesis Example 1, the polyamic acid solution (PAA2-1) obtained in Synthesis Example 7, and the polyamic acid solution (PAA3-3) obtained in Synthesis Example 24 were diluted with NMP, GBL, and BCS, and the additive (c-1) was added in an amount of 3 parts by mass relative to 100 parts by mass of all polymers, and the additive (s-1) was further added in an amount of 1 part by mass relative to 100 parts by mass of all polymers, and stirred at room temperature. Next, the obtained solution was filtered with a filter having a pore size of 0.5 μm, thereby obtaining a liquid crystal aligning agent (1) having a polymer component ratio of (SPI1-1): (PAA2-1): (PAA3-3) = 30: 40: 30 (solid content conversion mass ratio), a solvent composition ratio of NMP: GBL: BCS = 30: 35.5: 30 (mass ratio), and a polymer solid content concentration of 4.5% by mass (Table 3 below). Abnormalities such as turbidity and precipitation were not observed in this liquid crystal aligning agent, and it was confirmed that it was a uniform solution.
[0199] <Examples 2 to 33, Comparative Examples 1 to 7>
[0200] Liquid crystal aligning agents (2) to (33) and (R1) to (R7) were obtained in the same manner as in Example 1, except that the polymers shown in Table 3 below were used.
[0201] [Table 3]
[0202]
[0203] [Manufacturing of Liquid Crystal Display Element]
[0204] A liquid crystal cell having a structure of a fringe field switching (FFS) mode liquid crystal display element was produced.
[0205] First, a substrate with electrodes was prepared. The substrate was a glass substrate with a size of 35 mm × 40 mm and a thickness of 0.7 mm. On the substrate, as the first layer, an ITO electrode with a dense pattern constituting a counter electrode was formed. On the counter electrode of the first layer, as the second layer, a SiN (silicon nitride) film formed by a CVD method was formed. The film thickness of the second layer of SiN film was 500 nm, and it functions as an interlayer insulating film. On the second layer of SiN film, as the third layer, a comb-shaped pixel electrode formed by patterning the ITO film was arranged, forming two types of pixels, the first pixel and the second pixel. The size of each pixel is 10 mm in length and about 5 mm in width. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated due to the action of the second layer of SiN film.
[0206] The pixel electrode of the third layer has a comb-like shape formed by arranging a plurality of electrode elements in the shape of a "<" symbol with a bent central portion. The width of each electrode element in the short dimension direction is 3μm, and the interval between the electrode elements is 6μm. The pixel electrode forming each pixel is composed of a plurality of electrode elements in the shape of a "<" symbol with a bent central portion, so the shape of each pixel is not a rectangle, but a shape similar to a bold "<" symbol that is bent in the central portion like the electrode elements. In addition, each pixel is divided into upper and lower parts with the bent portion in the center as the boundary, and has a first area on the upper side of the bent portion and a second area on the lower side.
[0207] Comparing the first area and the second area of each pixel, the formation direction of the electrode elements constituting their pixel electrodes is different. That is, with the brushing direction of the liquid crystal alignment film described later as a reference, in the first area of the pixel, the electrode elements of the pixel electrode are formed in a manner to become an angle of +10° (clockwise), and in the second area of the pixel, the electrode elements of the pixel electrode are formed in a manner to become an angle of -10° (clockwise). That is, in the first area and the second area of each pixel, the directions of the rotational movement (in-plane / switching) of the liquid crystal within the substrate surface induced by the voltage application between the pixel electrode and the opposing electrode are configured to be opposite to each other.
[0208] Next, the liquid crystal orientation agent was applied by spin coating on the above-mentioned substrate with electrodes and a glass substrate with a columnar spacer having a height of 4 μm and an ITO film formed on the back, and the liquid crystal orientation agent was filtered by a 1.0 μm filter, and dried on a hot plate at 80°C for 2 minutes. Then, it was calcined in a hot air circulation oven at 230°C for 30 minutes to obtain a substrate with a liquid crystal orientation film with a film thickness of 100 nm. The surface of the substrate with the liquid crystal orientation film was brushed with rayon cloth (YA-20R made by Yoshikawa Chemical Industry) (roller diameter: 120 mm, roller speed: 1000 rpm, moving speed: 20 mm / sec, pressing length: 0.4 mm), and then irradiated with ultrasonic waves in pure water for 1 minute for cleaning. After removing water droplets by blowing, it was dried at 80°C for 15 minutes to obtain a substrate with a liquid crystal orientation film. The two substrates with liquid crystal alignment films obtained were used as a group, and the sealant was printed in the form of a liquid crystal injection port remaining on the substrate. The other substrate was bonded in a manner that the liquid crystal alignment film surface faced each other and the brushing direction became reversely parallel. Then, the sealant was cured to produce an empty cell with a cell gap of 4μm. Liquid crystal MLC-3019 (manufactured by MERCK) was injected into the empty box by the reduced pressure injection method, and the injection port was sealed to obtain an FFS-type liquid crystal display element. Then, the obtained liquid crystal display element was heated at 120°C for 1 hour, and left at 23°C overnight for evaluation.
[0209] [DC accumulation evaluation]
[0210] The FFS-driven liquid crystal cell produced above was placed between two polarizing plates arranged in an orthogonal manner, and the LED backlight was irradiated from below the two polarizing plates while the pixel electrode and the opposing electrode were short-circuited to be at the same potential, and the angle of the liquid crystal cell was adjusted so that the brightness of the LED backlight transmission light measured on the two polarizing plates was minimized. This evaluation was performed under the temperature condition that the temperature of the liquid crystal cell was 23°C.
[0211] Next, while applying an AC voltage of 30 Hz to the liquid crystal cell, the V-T curve (voltage-transmittance curve) was measured, and the AC voltage at which the relative transmittance became 23% or 100% was calculated as the driving voltage. A rectangular wave of 1 kHz and 20 mV was applied to the liquid crystal cell at 23°C for 30 minutes.
[0212] Then, an AC drive was applied for 45 minutes to make the relative transmittance 100%. During this time, the minimum offset voltage value was measured every 3 minutes, and the amount of change from the start of measurement to 45 minutes was calculated as the DC accumulation amount.
[0213] The accumulated charge affects the display as a disorder of the liquid crystal orientation and an afterimage, and the display quality level of the liquid crystal element is significantly reduced. Therefore, it can be said that the smaller the DC accumulation amount generated during driving, the better. In the present invention, the case where the DC accumulation amount is 150mV or less is considered to be particularly good.
[0214] [Relaxation characteristics of stored charge]
[0215] The FFS-driven liquid crystal cell produced above was placed between two polarizing plates arranged in an orthogonal manner, and the LED backlight was irradiated from below the two polarizing plates while the pixel electrode and the opposing electrode were short-circuited to be at the same potential, and the angle of the liquid crystal cell was adjusted so that the brightness of the LED backlight transmission light measured on the two polarizing plates was minimized. This evaluation was performed under the temperature condition that the temperature of the liquid crystal cell was 23°C.
[0216] Next, while applying an AC voltage of 30 Hz to the liquid crystal cell, the V-T curve (voltage-transmittance curve) was measured, and the AC voltage at which the relative transmittance became 23% or 100% was calculated as the driving voltage. A rectangular wave of 1 kHz and 20 mV was applied to the liquid crystal cell at 23°C for 30 minutes.
[0217] Then, while applying a rectangular wave with a frequency of 30 Hz to the liquid crystal box, the V-T characteristics (voltage-transmittance characteristics) at a temperature of 23°C were measured, and the AC voltage at which the relative transmittance becomes 23% was calculated. This AC voltage corresponds to the region where the change in brightness relative to the voltage is large, so it is appropriate to evaluate the stored charge through the brightness.
[0218] Next, a rectangular wave with a frequency of 30 Hz was applied for 5 minutes under an AC voltage to make the relative transmittance 23%, and then a DC voltage of +1.0 V was superimposed and driven for 30 minutes. Then, the DC voltage was cut off, and only a rectangular wave with a frequency of 30 Hz was applied for 30 minutes under an AC voltage to make the relative transmittance 23%.
[0219] The faster the relaxation of the accumulated charge, the faster the charge is accumulated in the liquid crystal box when the DC voltage is superimposed. Therefore, the relaxation characteristics of the accumulated charge are evaluated by the time required for the relative transmittance to drop from a state of more than 30% to 23% just after the DC voltage is superimposed. It can be said that the shorter the time, the better the relaxation characteristics of the accumulated charge. Specifically, the time from the time when the DC voltage is applied to the time after 30 minutes, the time for the relative transmittance to drop below 30% is quantified. The case where the relative transmittance drops below 30% within 10 minutes is evaluated as "◎", if it exceeds 10 minutes and within 20 minutes, it is evaluated as "○", if it exceeds 20 minutes and within 30 minutes, it is evaluated as "△", and the case where the relative transmittance does not drop below 30% in 30 minutes is evaluated as "×".
[0220] [Evaluation of afterimage characteristics based on long-term AC drive]
[0221] The prepared FFS drive liquid crystal cell was subjected to an AC voltage of ±5 V at a frequency of 60 Hz for 120 hours at a constant temperature of 60° C. Then, the pixel electrode and the counter electrode of the liquid crystal cell were short-circuited and left at room temperature for one day.
[0222] Regarding the liquid crystal cell subjected to the above-described processing, the deviation between the alignment direction of the liquid crystal in the first region of the pixel and the alignment direction of the liquid crystal in the second region in the state where no voltage is applied is calculated as an angle.
[0223] Specifically, a liquid crystal box is set between two polarizing plates arranged in an orthogonal manner, the backlight is turned on, and the configuration angle of the liquid crystal box is adjusted in such a way that the transmitted light intensity of the first area of the pixel is minimized. Then, the rotation angle required to rotate the liquid crystal box in such a way that the transmitted light intensity of the second area of the pixel is minimized is calculated.
[0224] It can be said that the smaller the value of the rotation angle, the better the afterimage characteristics based on long-term AC driving. Specifically, the case where the rotation angle is 0.5 degrees or less is evaluated as "◎", the case where the rotation angle exceeds 0.5 degrees and is 1.0 degrees or less is evaluated as "○", the case where the rotation angle exceeds 1.0 degrees and is 1.5 degrees or less is evaluated as "△", and the case where the rotation angle further exceeds 2.0 degrees is evaluated as "×".
[0225] [Evaluation of optical properties (transparency)]
[0226] A quartz substrate of 40 mm × 40 mm in size and 1.0 mm in thickness was prepared. Then, the liquid crystal alignment agent was filtered using a 1.0 μm filter and then spin-coated on the quartz substrate. Then, it was dried on a hot plate at 80°C for 2 minutes and calcined at 230°C for 20 minutes to obtain a polyimide film of 100 nm in thickness on each substrate.
[0227] The transparency is evaluated by measuring the transmittance of the substrate obtained by the method. Specifically, the measuring device uses UV-3600 (manufactured by Shimadzu Corporation) and measures the transmittance under the conditions of a temperature of 25°C and a scanning wavelength of 300 to 800nm. At this time, a quartz substrate not coated with any substance is used in the reference (reference example). For evaluation, the average transmittance of the wavelength of 400 to 800nm is calculated. The higher the transmittance, the better the transparency.
[0228] The evaluation results of the DC storage amount, the relaxation characteristics of the stored charge, the afterimage characteristics by long-term AC driving, and the optical characteristics of the liquid crystal display elements using the liquid crystal aligning agents of Examples 1 to 33 and Comparative Examples 1 to 7 are shown in Table 4 below.
[0229] [Table 4]
[0230]
[0231] It can be seen that the liquid crystal display element using the liquid crystal aligning agent of the Example of the present invention suppresses the DC accumulation amount and achieves high compatibility with other characteristics.
[0232] Industrial Applicability
[0233] The liquid crystal aligning agent of this invention is useful for forming a liquid crystal aligning film in a wide range of liquid crystal display elements, such as an IPS drive system and an FFS drive system.
[0234] It should be noted that all the contents of the specifications, claims, and abstracts of Japanese Patent Application No. 2019-014146 filed on January 30, 2019 and Japanese Patent Application No. 2019-100642 filed on May 29, 2019 are incorporated herein by reference and are incorporated as a disclosure of the specification of the present invention.
Claims
1. A liquid crystal alignment agent, characterized in that: Containing: the following polymer A, polymer B and polymer C, Polymer A: at least one polymer selected from the group consisting of the following (i) and (iii), (i) a polyamic acid obtained by polymerizing a diamine component containing at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the following formula [2], wherein the tetracarboxylic acid component is composed of an aromatic tetracarboxylic dianhydride, (iii) a polyimide obtained by imidizing a polyimide precursor obtained by polymerizing a diamine component and a tetracarboxylic acid component, wherein the diamine component contains at least one diamine selected from the group consisting of a diamine represented by the following formula [1] and a diamine represented by the following formula [2], In formulas [1] and [2], A1 is a single bond, an ether bond, an ester bond, -C=C-, -C≡C-, an alkylene group having 2 to 20 carbon atoms, or a group in which a part or all of -CH2- in the alkylene group is substituted with at least one group selected from the group consisting of an ether bond, an ester bond, -C=C-, -C≡C-, a cyclohexylene group and a phenylene group, a cyclohexylene group or a phenylene group; A2 is an alkyl group or an alkoxy group having 1 to 5 carbon atoms; a is an integer of 0 to 4. When a is an integer of 2 or more, A2 may be the same or different; b and c are each independently an integer of 1 to 2; Polymer B: at least one polymer selected from the group consisting of a polyimide precursor obtained by polymerizing a diamine component and a tetracarboxylic acid component, and a polyimide obtained from the polyimide precursor, wherein the diamine component contains a diamine represented by the following formula [3], H2N-X-NH2 [3] In the formula, X has a structure in which an aromatic hydrocarbon ring is bonded to a carbon atom constituting a five-membered or six-membered nitrogen-containing aromatic heterocyclic ring, or has a structure represented by the following formula: * Bonded to a structure other than a carbonyl group, and at least one bonded to an aromatic ring group, Polymer C: A polyamic acid obtained by polymerization reaction of a diamine component and a tetracarboxylic acid component, wherein the diamine component does not contain the diamine represented by the formula [3] and the tetracarboxylic acid component is composed of an alicyclic tetracarboxylic dianhydride and / or an aliphatic tetracarboxylic dianhydride.
2. The liquid crystal alignment agent according to claim 1, wherein In the above formulae [1] and [2] in the polymer A, A1 is a single bond, an alkylene group having 2 to 20 carbon atoms, or a group in which a part or all of -CH2- in the alkylene group is substituted with at least one group selected from the group consisting of an ether bond and a phenylene group.
3. The liquid crystal aligning agent according to claim 1 or 2, wherein: In the formulas [1] and [2] in the polymer A, A1 is a single bond, an alkylene group having 1 to 10 carbon atoms, or a phenylene group, wherein at least one -CH2- of the alkylene group is substituted with an ether group or an ester group, A2 is CH3, a is an integer of 0 to 1, b is 1, and c is an integer of 1 to 2.
4. The liquid crystal aligning agent according to claim 1 or 2, wherein The amount of the diamine represented by the formula [1] and [2] used is 30 to 100 mol % based on the total amount of the diamine component used to produce the polymer A.
5. The liquid crystal aligning agent according to claim 1 or 2, wherein The diamine represented by the formula [3] in the polymer B has structures represented by the following formulas [3-1] to [3-3], In the formula, * represents a bond, and in the formula [3-3], at least one of the bonds derived from the carbon atom constituting the nitrogen-containing aromatic heterocyclic ring is bonded to the aromatic hydrocarbon ring.
6. The liquid crystal aligning agent according to claim 1 or 2, wherein: The diamine represented by the formula [3] in the polymer B is selected from the group consisting of the following diamines:
7. The liquid crystal aligning agent according to claim 1 or 2, wherein: The diamine component in the polymer C includes a diamine represented by the following formula [4]: H2N-Y-NH2 [4] In the formula, Y has any one or more structures represented by the following formulae, * is a bonding bond, 8. The liquid crystal alignment agent according to claim 7, wherein: The diamine represented by the formula [4] is a diamine selected from the group consisting of the following formulas:
9. The liquid crystal alignment agent according to claim 1 or 2, wherein: The tetracarboxylic acid component in the polymer A (iii) is composed of aromatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aliphatic tetracarboxylic dianhydride or derivatives thereof.
10. The liquid crystal aligning agent according to claim 1 or 2, wherein The tetracarboxylic acid component in the polymer A (iii) is composed of alicyclic tetracarboxylic dianhydride, aliphatic tetracarboxylic dianhydride or derivatives thereof.
11. The liquid crystal alignment agent according to claim 1 or 2, wherein The aromatic tetracarboxylic dianhydride in the polymer A is a compound represented by the following formula (3a-1): In the above formula, X1 is any of the following formulae (A-1) to (A-12) and (A-14) to (A-28), * represents a bonding bond, 12. The liquid crystal alignment agent according to claim 1 or 2, wherein: The alicyclic tetracarboxylic dianhydride and / or aliphatic tetracarboxylic dianhydride in the polymer C is a compound represented by the following formula (3c-1): In the above formula, X2 is any of the following formulas (B-1) to (B-18), * represents a bonding bond, 13. The liquid crystal aligning agent according to claim 1 or 2, wherein: The polymer A is contained in an amount of 10 to 50% by mass based on 100% by mass of the total amount of the polymers A to C.
14. The liquid crystal aligning agent according to claim 1 or 2, wherein: The polymer B is contained in an amount of 10 to 70% by mass based on 100% by mass of the total amount of the polymers A to C.
15. The liquid crystal alignment agent according to claim 1 or 2, wherein: The polymer C is contained in an amount of 10 to 50% by mass based on 100% by mass of the total amount of the polymers A to C. 16 . A liquid crystal alignment film obtained from the liquid crystal alignment agent according to claim 1 . 17 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 16 .
